The Effect of Using Difermented Dragon Fruit Leather Flour In Saccharomyces cerevisiaeon Organs In Broiler - M.I, Mayana; G.A.M.K., Dewi; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study aims to determine the effect of using by Saccharomyces cerevisiae fermented fruit skin flour in rations on broiler organs. The study was conducted at the Faculty of Animal Husbandry Research Station of Udayana University, Jimbaran, Badung, Bali for 5 weeks.Research using broilers type MB 202 take from PT Japfa Comfeed Indonesia Tbk. One week old (DOC) as many as 90 tails with homogeneous body weight. The design used was a completely randomized design (CRD) with 3 treatments and 6 replications, where each replication consisted of 5 broilers. The treatment tried in this study was RKBN0 ration without dragon fruit skin, RKBN1 ration with 5% fermented dragon fruit skin, RKBN2 ration with 7% fermented dragon fruit skin. Variables observed were heart weight, liver weight, spleen weight and bile weight. The results showed that the treatment of RKBN1 and RKBN2 received lower internal organs (heart, liver, spleen and bile) compared to RKBN0, but it was not statistically different (P> 0.05). Based on the results of the study it can be concluded that the use of dragon fruit peel flour as much as 5% and 7% no effect on broiler organs in the age of 5 weeks.Keywords : Broilers,internal organs, fermented dragon fruit skin flour,Saccharomyces cerevisie